Pengaruh Fraksi Volume Serat Kayu Gelam (Melaleuce Leucandendra) terhadap Kekuatan Tarik dan Impak Komposit Bermatrik Polyester - Arief, Saifullah; Pratikto, Pratikto; Irawan, Yudy Surya (Jurnal Rekayasa Mesin, 2016)
The purpose of this research is to find the effect of volume fraction variation of â€œgelamâ€ bark fiber on tensile and impact strength of polyester composite. The filler material was the â€œgelamâ€ bark fiber with volume variation ratio of 10%, 30 %, 50 % and 70 %. Alkalization of the â€œgelamâ€ bark fiber used 5% of NaOH and 2 hours of soaking time. Mechanical testing was carried out by tensile and impact testing. The matrix for bonding the â€œgelamâ€ bark fiber was polyester resin type 157 BTQN and 1% concentration of MEKPO catalyst. The mechanical properties are obtained from tensile and impact testing: The results of tensile testing; slowed the highest tensile strength of compositre with 70% of â€˜gelam bark fiber was 15.623 MPa. The results of impact testing: obtained the highest impact strength in composete with 70 % percentage of â€˜gelamâ€™ bark fiber is24.772 J.